Frontline perceptions, practices and experiences of community pharmacists in Nigeria during the COVID-19 pandemic - Ayodapo O. Jegede; Aishat A. Quadri; Kayode T. Olabanji (Discover Public Health)
Abstract Community pharmacists in Nigeria were pivotal to COVID-19 public health efforts, making their perceptions and practices key to shaping effective strategies. This study examined the role of community pharmacists in Nigeria during the COVID-19 crisis by exploring their beliefs, practices, and experiences, evaluating demographic influences on their perceptions, and identifying key contributions to pandemic response efforts. A cross-sectional survey was conducted among 372 licensed pharmacists selected through proportionate random sampling from Nigeria’s northern and southern regions. Data were collected using a pre-tested, semi-structured questionnaire. Descriptive statistics, Mann-Whitney U, and Kruskal-Wallis tests were used to examine associations at a significance level of p ≤ 0.05. Findings show a high knowledge level across key items, with median scores of 5.0 (IQR 5–5) for beliefs that COVID-19 is a viral infection, affects the respiratory system, and originated in Wuhan. Misconceptions persisted on whether the disease affects only the elderly or chronically ill, with lower medians of 1.0 (IQR 1–5 and 1–2, respectively). Natural remedy belief had a median of 3.0 (IQR 2–4). Most pharmacists (83.6%) reported conducting sensitization activities, and 84.9% used masks and gloves. Perceptions of their role were overwhelmingly positive, with a median of 5.0 (IQR 5–5) for all role-related items. Regional differences were largely non-significant, except for suspected cases reported in pharmacies (U = 12,290.0, p = 0.009), which were more frequent in the South. The study concludes that community pharmacists in Nigeria played a pivotal role during the COVID-19 pandemic, particularly in public health sensitization, adherence to safety protocols, and fostering interdisciplinary collaboration. It also highlights demographic factors influencing their perceptions and practices while addressing challenges such as hostility and misconceptions surrounding home therapy.